Acute acalculous cholecystitis as a rare manifestation of chronic mesenteric ischemia : a case report - Melo, Ryan (2016)
© 2016 The Authors.Published by Elsevier Ltd on behalf of IJS Publishing Group Ltd. This is an open access article under the CCBY-NC-NDlicense(http://creativecommons.org/licenses/by-nc-nd/4.0/)